Pengembangan Kemampuan Kreatif Produktif Siswa SMA Fides Kefamenanu melalui Pelatihan Jurnalistik - Sahan, Anselmus; Sahan, Meylisa Yuliastuti; Kamlasi, Imanuel; Wisrance, Maria Wihelmina; Tenis, Wilfridus; Manu, Hendrik O (LPPM Universitas Timor, 2024)
The implementation of this PkM was carried out using socialization, lecture, training (workshops), and guidance methods. After giving the training, the students were presented with a questionnaire containing 7 questions to find out their perceptions of the benefits of the training for the development of their creative-productive abilities. Their answers were analyzed using descriptive qualitative, namely the number of answers divided by the number of students multiplied by 100%. The results of the data analysis showed that 50 (or: 26%) respondents were very capable, 88 (or; 47%) were able, 47 (or: 25%) were less able and 4 (or: 2%) were unable. This shows that all respondents have benefited from journalistic training which is useful for developing creative-productive critical thinking skills. In addition, there are two digital journalistic skills that they are good at, namely using a laptop/computer (17 answers or 63%) and publishing works via Instagram (15 answers or 56%). This happens because they have been familiar with various digital technology tools and used them well. These results have implications for the use of digital technology facilities in subsequent journalistic training and teaching and learning processes in the classroom.